Nawrócenie św. Augustyna a jego stosunek do kultury antycznej - Spychała, Dariusz (Studia Europaea Gnesnensia, 2011)
Augustine of Hippo was the most eminent Church theologian at the close of antiquity. His influence is perceptible until the present day. The path which led him to Christianity was typical for the period of the late Roman Empire, when various religious currents would contend. It seems that the problems of antique culture were of secondary significance in his conversion.